Family history and outcome of young patients with breast cancer in the UK (POSH study). Issue 8 (20th May 2015) - Eccles, B K; Copson, E R; Cutress, R I; Maishman, T; Altman, D G; Simmonds, P; Gerty, S M; Durcan, L; Stanton, L; Eccles, D M; Eccles, D; Simmonds, P; et al.
Abstract: Background: Young patients presenting to surgical clinics with breast cancer are usually aware of their family history and frequently believe that a positive family history may adversely affect their prognosis. Tumour pathology and outcomes were compared in young British patients with breast cancer with and without a family history of breast cancer. Methods: Prospective Outcomes in Sporadic versus Hereditary breast cancer (POSH) is a large prospective cohort study of women aged less than 41 years with breast cancer diagnosed and treated in the UK using modern oncological management. Personal characteristics, tumour pathology, treatment and family history of breast/ovarian cancer were recorded. Follow-up data were collected annually. Results: Family history data were available for 2850 patients. No family history was reported by 65·9 per cent, and 34·1 per cent reported breast/ovarian cancer in at least one first- or second-degree relative. Patients with a family history were more likely to have grade 3 tumours (63·3 versus 58·9 per cent) and less likely to have human epidermal growth factor receptor 2-positive tumours (24·7 versus 28·8 per cent) than those with no family history. In multivariable analyses, there were no significant differences in distant disease-free intervals for patients with versus those without a family history, either for the whole cohort (hazard ratio (HR) 0·89, 95 per cent c.i. 0·76 to 1·03; P = 0·120) or when stratified by oestrogen receptor (ER) status (ER-negative: HR 0·80, 0·62 to 1·04, P = 0·101; ER-positive: HR 0·95, 0·78 to 1·15, P = 0·589). Conclusion: Young British patients presenting to breast surgical clinics with a positive family history can be reassured that this is not a significant independent risk factor for breast cancer outcome. Abstract : Family history does not influence outcome